Pleural Effusion: Characterization With contrast CT Appearance and CT Attenuation Values - Jasim, Ali H.; Fahad, Qusai A.; Jabbar, Jinan A. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: A number of different types of fluid may accumulate in the pleural space, the most common being transudate, exudate (thin or thick), blood and chyle. All types of pleural effusion are radio graphically identical, though historical, clinical and other radiological features may help limit the diagnostic possibilities. Sometimes, also CT and MRI can help to specify the diagnosis.Objective: To determine the accuracy of computed tomography (CT) in enabling differentiation of pleural exudates from transudates.Patients and methods: forty three consecutive patients (43 effusions) underwent contrast-enhanced CT. Thoracocentesis was performed to measure pleural and serum total protein values. Effusions were classified as exudates with accepted criteria. CT scans were evaluated for the presence and appearance of: parietal pleural thickening, visceral pleural, thickening, extra pleural fat thickening, measurement of CT attenuation values for each of the pleural fluids.Results: 34 effusions were exudates and 9 were transudates. Twenty of the 34 exudates (59%) were associated with parietal pleural thickening. 67% of empyema and 86% of the parapneumonic exudative effusions had pleural thickening. The specificity of this finding in diagnosing the presence of an exudate is 88%. The mean value in Hounsfield units of an effusion was determined using a region of interest on the three slices with the greatest quantity of fluid.Conclusion: Ultrasound is done to detect pleural effusion ,which sometimes cannot be detected by conventional radiography , but characterization of the pleural fluid cannot be done by ultrasound because CT attenuation with additional pleural CT appearance features such as fluid loculation, pleural thickness, and pleural nodules are helpful in differentiating exudates from transudates, because we found that their prevalence is higher among exudative effusions .so ultrasound is done to detect the effusion ,but its characterization is done by CT.